PERFORMANCE COMPARISON OF ASYMMETRIC CRYPTOGRAPHY (CASE STUDY-MAIL MESSAGE) - Sann, Zarni; Soe, Thi thi; Knin, Kaythi Wyut Mhone; Win, Zin May (APTIKOM Journal on Computer Science and Information Technologies, 2019)
Data encryption is well known as essential for today?s technology. ElGamal encryption and RSA algorithmis made before storing mails to mail server. ElGamal decryption and RSA decryption is made after retrieving mailsfrom mail server. This system is implemented to secure mail server system for local government?s important mailmessages. These algorithms consume a considerable amount of time and resources of memory, CPU time, andcomputation time to encrypt and decrypt data. This paper discuss the results comparison of these algorithms in termof encryption time, decryption time, and memory usage over variable file sizes. The results show that RSA does fasterencryption process in compare with ElGamal. However, ElGamal decryption process is quicker than RSA. This systemis also expressed comparison of storage Size between RSA and ElGamal. Both of these algorithms are cryptographicpublic-key algorithms but have roles in different techniques. This system is using C# programming language and SQLServer to store mail messages.